Observation of Biexcitons in Time-Resolved Degenerate-Four-Wave-Mixing on GaAs Quantum Wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Kuhl, J.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
Although the importance of exciton/exciton interactions for the nonlinear optical response of GaAs quantum wells (QW) is well established by many experimental observations, the role of biexciton states in these processes is still an open question, even at low excitation densities. Evidence for the formation of biexcitons has been independently derived from pump-probe studies [1], from the density dependence of the photoluminescence (PL) line shape [2] and from signal modulations observed in degenerate-four-wave-mixing (DFWM) with incoherent light pulses [3]. Here, we report on time-resolved DFWM with parallel (PP) and cross-polarized (CP) pulses. Depending on the polarization geometry, the signals reveal strong quantum beats which correspond to the splitting between either the heavy hole (hh) and light hole (lh) exciton or the hh exciton and the biexciton.

Field-induced dynamics of a wave packet in a wide superlattice miniband - Meier, Torsten; von Plessen, G.; Feldmann, J.; Göbel, E.O.; Thomas, P.; Goossen, K.W.; Kuo, J.M.; Kopf, R.F. (International Quantum Electronics Conference)
In the absence of scattering mechanisms, a crystal electron subjected to a homogeneous electric field undergoes a periodic motion in both momentum and real space. This oscillatory motion is known as Bloch oscillations (BOs) and has recently been detected in transient four-wave mixing (FWM) and Tera-Hertz emission experiments on semiconductor superlattices. It is generally assumed that the minimum field required for the observation of BOs is controlled by the rate of scattering in the material. However, an experimental verification of this point is still lacking.

Direct verification of the existence of biexcitons in GaAs qauntum wells - Meier, Torsten; Smith, G.O.; Mayer, E.J.; Kuhl, J.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (European Quantum Electronics Conference)
The strong nonlinear optical response of the 2D exciton in GaAs quantum wells at relatively low excitation densities has been observed in many experimental studies in accordance with theoretical predictions. In principle, exciton/exciton interaction results in a renormalization of the transition matrix elements, dephasing rates and frequencies of the excitonic states. Wang et al.1 claimed that all experimental results can be explained by a density- induced enhanced dephasing rate. In a previous paper,2 we have suggested a density dependent coupling between opposite spin excitons, which involves all three renormalization phenomena.

Kreativität und Reproduktion. Annäherung an den Bildungshorizont von Ursula Weida - Schuster, Britt-Marie (Bausteine zu einer Geschichte des weiblichen Sprachgebrauchs. Forschungsberichte – Projektangebote – Forschungskontexte)
Keywords: Sprachliche Formelhaftigkeit/-Musterhaftigkeit

Die Artes liberales im frühen Mittelalter (5.-9. Jh.). Das Quadrivium und der Komputus als Indikatoren für Kontinuität und Erneuerung der exakten Wissenschaften zwischen Antike und Mittelalter - Englisch, Brigitte

Problem Independent Distributed Simulated Annealing and its Applications - Diekmann, Ralf; Simon, Jens (Applied Simulated Annealing)

Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk

Stanislaw Przybyszewski: Schnee und andere Dramen (Edition) - Eke, Norbert Otto

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 7. Aufzeichnungen. Vermischte Schriften. Text und Kommentar (Edition) - Eke, Norbert Otto; Oellers, Norbert; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Rettung des Sinns. Jaákobs Traum und das Projekt einer Geschichtstheodizee - Eke, Norbert Otto (Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk)

Richard Beer-Hofmann – Zur Einführung - Eke, Norbert Otto; Helmes, Günter (Richard Beer-Hofmann (1866-1945). Studien zu seinem Werk)

„Freiheit ist nur in dem Reich der Träume“. Revolutionsprojektionen deutscher Dramen nach 1789. Ein historischer Aufriß (mit einem Ausblick bis zum Nachmärz) - Eke, Norbert Otto (Grabbe Jahrbuch 12)

Eine Gesamtbibliographie des deutschen Romans 1815-1830. Anmerkungen zum Problemfeld von Bibliographie und Historiographie - Eke, Norbert Otto (Zeitschrift für Germanistik)

„Deutschland ortlos“. Dekonstruktionen des Nationalen bei Heiner Müller - Eke, Norbert Otto (Dichter und ihre Nation)

Continuous Mixture Densities and Linear Discriminant Analysis for Improved Context-Dependent Acoustic Models - Aubert, Xavier L.; Haeb-Umbach, Reinhold; Ney, Hermann (ICASSP, Minneapolis)
Linear discriminant analysis (LDA) experiments reported previously (ICASSP-92 vol.1, p.13-16), are extended to context-dependent models and speaker-independent large vocabulary continuous speech recognition. Two variants of using mixture densities are compared: state-specific modeling and the monophone-tying approach where densities are shared across the states relevant to the same phoneme. Results are presented on the DARPA Resource Management (RM) task for both speaker-dependent (SD) and speaker-independent (SI) parts. Using triphone models based on LDA and continuous mixture densities, significant improvements have been observed and the following word error rates have been achieved: for the SD part, 7.8% without grammar and 1.5% with word pair; and for the SI part, 17.2% and 4.6%, respectively. These scores are averaged over 1200 SD or SI evaluation sentences and are among the best published so far on the RM database.

The Philips Research System for Large-Vocabulary Continuous-Speech Recognition - Steinbiss, Volker; Ney, Hermann; Haeb-Umbach, Reinhold; Train, B.-H.; Essen, U.; Kneser, Reinhard; Oerder, Martin; Meier, H. G.; Aubert, X.; Dugast, Christian; Geller, Dieter; Hoellerbauer, W.; et al. (EUROSPEECH, Berlin)
This paper gives a status report of the Philips research system for phoneme-based, large-vocabulary, continuous-speech recognition. Like for many other systems, the recognition architecture is based on an integrated statistical approach. We describe the characteristic features of the system as opposed to other systems: 1. The Viterbi criterion is consistently applied both in training and testing. 2. Continuous mixture densities are used without tying or smoothing. 3. Time-synchronous beam search in connection with a phoneme look-ahead is applied to a tree-organized lexicon. The system has been successfully applied to the American English DARPA RM task. Here, we report experimental results for a German 13 000-word Philips internal dictation task. In addition to the scientific prototype, a PC version has been set up which is described here for the first time.

Chemisorption of aluminium on GaAs(110) - Schmidt, Wolf Gero; Srivastava, G P (Journal of Physics: Condensed Matter)

́Augen wie Leuchtkäfer ́ - Zur Sprache der Liebe in Mario Vargas Llosas ́ Lob der Stiefmutter - Öhlschläger, Claudia (Rundbrief Frauen in der Literaturwissenschaft 37. Mai 1993: Sprachen der Liebe)

Loser und fester Anschluß. Versuch der Neubewertung einer abgelegten Kategorie - Maas, Utz; Tophinke, Doris (Sprachwandel und Sprachgeschichte. FS für Helmut Lüdtke)

Sprachentwicklung in Geschichte und Gegenwart - Maas, Utz; Frankenbusch, Marita; Johannlückens, Ralf; Stöwer-Gaus, Ursula; Striezel, Marion; Tophinke, Doris (Damme. Eine Stadt in ihrer Geschichte)